Transcriptional repression of the oncofetal LIN28B gene by the transcription factor SOX6 - Pastori, Valentina; Zambanini, Gianluca; Citterio, Elisabetta; Weiss, Tamina; Nakamura, Yukio; Cantù, Claudio; Ronchi, Antonella Ellena (Scientific reports, 2024)
The identification of regulatory networks contributing to fetal/adult gene expression switches is a major challenge in developmental biology and key to understand the aberrant proliferation of cancer cells, which often reactivate fetal oncogenes. One key example is represented by the developmental gene LIN28B , whose aberrant reactivation in adult tissues promotes tumor initiation and progression. Despite the prominent role of LIN28B in development and cancer, the mechanisms of its transcriptional regulation are largely unknown. Here, by using quantitative RT-PCR and single cell RNA sequencing data, we show that in erythropoiesis the expression of the transcription factor SOX6 matched a sharp decline of LIN28B mRNA during human embryo/fetal to adult globin switching. SOX6 overexpression repressed LIN28B not only in a panel of fetal-like erythroid cells (K562, HEL and HUDEP1; ≈92% p < 0.0001, 54% p = 0.0009 and ≈60% p < 0.0001 reduction, respectively), but also in hepatoblastoma HepG2 and neuroblastoma SH-SY5H cells (≈99% p < 0.0001 and ≈59% p < 0.0001 reduction, respectively). SOX6-mediated repression caused downregulation of the LIN28B/Let-7 targets, including MYC and IGF2BP1 , and rapidly blocks cell proliferation. Mechanistically, Lin28B repression is accompanied by SOX6 physical binding within its locus, suggesting a direct mechanism of LIN28B downregulation that might contribute to the fetal/adult erythropoietic transition and restrict cancer proliferation.